lncRNA LINC01206 regulates the cell cycles in psoriasis - Jingxia LIN; Fangfei ZHANG; Zeqiao ZHANG; Yuanqiu ZHONG; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective To explore the function and mechanism of lncRNA on the cell cycles in psoriasis. Methods We first identified the differentially expressed genes through integrative analysis of RNA-seq datasets from a psoriasis cohort. Then KEGG analysis was performed to identify the key signaling pathways in psoriasis. WGCNA was used to construct the lncRNA-protein coding genes (PCGs) co-expression network. A specific siRNA was used to knockdown LINC01206 in HaCaT keratinocytes and the cell cycle progression was detected by flow cytometry. Results Integrative analysis of RNA-seq datasets from the psoriasis cohort demonstrated a dysregulation of the cell cycle pathway in psoriasis. Moreover, lncRNA-protein coding gene (PCGs) co-expression analysis showed that LINC01206, LINC01269, LINC01215and LINC02159 interacted with the key factors CCNA2, CCNB1 and CCNE1, in cell cycle pathway to regulate the progress of psoriasis. Flow cytometry analysis showed that knockdown of LINC01206 induced cell cycle arrest at the G2/M phase. Conclusions Our results demonstrate the functional mechanism of lncRNAs in the cell cycle. LncRNA may be a therapeutic target for psoriasis.